The effect of shocks on household consumption in rural Nigeria - Abdulaziz, Shehu; Ahmad Sidique, Shaufique Fahmi (Australian Academy of Business and Social Sciences, 2014)
This paper examines the impact of both exogenous idiosyncratic and covariate shock events on the consumption of farm households in rural Nigeria by using an ordinary least square method. The result of the overall sample shows that whilst idiosyncratic and climatic shock have no significant effect on household consumption, price shocks are having a significant negative impact on household consumer. By disaggregating the sample into poor and non-poor households the result suggests that that the non-poor households are able to adequately insure against the effect of idiosyncratic shocks as well as the climatic shock on their consumption while the poorer ones had not been able to insure against the effect of shocks related to death, livestock loss, climate change and price changes on their consumption. This suggests that the farm households should be provided with an adequate and effective social protection measures that would mitigate the effect of shocks on their welfare.